PERAN GURU KREATIF: IMPLEMENTASI SMART TABLETS UNTUK MATERI IPAS TENTANG SEJARAH KERAJAAN DI INDONESIA - Permana, Wahid Bayu; Ningsih, Tutuk (Jurnal Dedikasi Pendidikan, 2025)
The purpose of this study is to outline how innovative educators are utilizing smart tablets as a teaching tool for Natural and Social Sciences (IPAS) content pertaining to Indonesian kingdom history at MIN 1 Banyumas. Twenty-five fifth-grade kids made up the sample used in this study. Purposive sampling was the method employed to choose students who participated in science education using smart tablets. This study used documentation, teacher and student interviews, and observation as data gathering methods. Interviews were conducted to see how teachers and students felt about using smart tablets, observations were made to observe how technology was used in the classroom, and documentation was done to back up the findings. To thoroughly explain the use of smart tablets in Indonesian royal history education, the gathered data was examined using a qualitative descriptive methodology. According to the study's findings, using smart tablets can help teachers develop more engaging and interactive lessons while also boosting students' enthusiasm and engagement with royal history content. Teachers can use technology in innovative ways to help pupils grasp difficult subjects. According to the study's findings, MIN 1 Banyumas' use of smart tablets in science instruction has improved student engagement, learning quality, and digital literacy